THE ENHANCEMENT OF THE CAPACITY OF COMMUNITIES AROUND THE FOREST IN PRODUCING ANIMAL FEED THROUGH SILAGE-MAKING TRAINING - Budiyoko, Budiyoko; Syamsi, Afduha Nurus; Sunendar, Sunendar; Zulkifli, Lutfi; Rachmah, Malinda; Madiyoh, Abdulhakim (Universitas Airlangga, 2024)
Kemutug Lor Village, located on the southern slope of Mount Slamet, boasts various potentials, including livestock farming and the utilization of forest resources. One method of forest area management undertaken by the community is the development of an agrosilvopastoral model, which integrates seasonal crop cultivation with forestry and livestock activities. This community service initiative aims to enhance the community's capacity in processing odot grass into silage as high-quality animal feed. The approach utilized in this activity is asset-based community development. Goat farming and the development of the agrosilvopastoral model in the forest area, initiated by the community, serve as the foundation for this community service activity. A total of 23 individuals from the community were equipped with technical skills in silage production using odot grass as the raw material. This endeavor contributes to the utilization of abundant odot grass in Kemutug Lor and the enhancement of livestock feed management within the community. Evaluation results indicate an increase in the community's knowledge of silage production after receiving training materials. Furthermore, subsequent to the conclusion of the training activity, the community engages in periodic practice and production of silage as supplementary animal feed.